(untitled) (Web of Teachers: Inderscience Research, 2026)
Soviet literature of the 20th century, unlike world literature, was created on the basis of a single literary direction - the principles of socialist realism. Only a few creators were able to create works that would serve all eras equally with the requirements that socialist realism placed on literature. Chingiz Aitmatov was one of them. One of the most important services of the writer is that he initiated the tradition of expressing his great sorrows and ideas through the images of "little people". Also, his attitude to objective reality was realized through the synthesis of the genres of mythology, folklore, and fiction in his stories and novels.